Photolithographic fabrication of graphene-based all-solid-state planar on-chip microsupercapacitors with ultrahigh power characteristics - Zhang, Ludi; Liu, Linjing; Liu, Chunfeng; Li, Xiang; Liu, Fangshuo; Zhao, Wenqiang; Wang, Shu; Wu, Fengmin; Zhang, Guangyu (Journal of applied physics, 2019)
The fabrication of all-solid-state planar on-chip microsupercapacitors with ultrahigh power characteristics was demonstrated by reduced graphene oxide and photolithography technology. In this paper, an ultrathin reduced graphene oxide film with a thickness of 8 nm was prepared by a modified spin coating method that makes the microsupercapacitors have higher power characteristics which appear in high conductivity and fast charge and discharge rates. The electrodes, with a width of 150 μm, are narrower than existing electrodes in the field and fabricated by photolithography. In terms of performance, these microsupercapacitors have an extremely short time constant which is 0.03 ms, a high power density which is 17.94 W cm−3, and an excellent cycle stability with a capacitance retention of 94.6% after 10 000 cycles.